2013
DOI: 10.15407/ubj85.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxidative stress on the level of genes expression TGFB1 and HGF in rat liver upon long-term gastric hypochlorhydria and administration of multiprobiotic Symbiter

Abstract: Досліджено вільнорадикальні процеси в печінці щурів під час тривалої шлункової гіпохлоргідрії, спричиненої омепразолом. встановлено підвищення інтенсивності окислювальних процесів у тканині печінки: надлишкове утворення супероксидного аніона, пероксиду водню, кількісні зміни функціональних груп ліпідів, зростання вмісту продуктів пероксидного окислення ліпідів, збільшення ксантиноксидазної активності. показано, що експресія гену Tgfb1 зростає, а експресія гену Hgf не виявляється, що свідчить про можливий розви… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…A previous study has suggested that TGFB is a crucial regulator of central nervous system development (Gomes et al, 2005). It has been found that the level of TGFB1 affected oxidative stress in rat liver (Dvorshchenko et al, 2013). After PAMAM dendrimer exposure, the expression of TGFB1 was greatly inhibited, inferring that dendrimer treatment may affect oxidative stress in cells and human central nervous system development.…”
Section: A B C Dmentioning
confidence: 97%
“…A previous study has suggested that TGFB is a crucial regulator of central nervous system development (Gomes et al, 2005). It has been found that the level of TGFB1 affected oxidative stress in rat liver (Dvorshchenko et al, 2013). After PAMAM dendrimer exposure, the expression of TGFB1 was greatly inhibited, inferring that dendrimer treatment may affect oxidative stress in cells and human central nervous system development.…”
Section: A B C Dmentioning
confidence: 97%
“…Hypochlorhydria may, in fact, be more common in the aging population as the gut physiology changes [64], and the use of certain medications can also impact hydrochloric acid levels [65]. Further, oxidative stress (such as seen with low physiological glutathione levels) [66,67] and certain nutrient deficiencies [68] may also contribute to low stomach acid levels.…”
Section: Dietary Protein Considerationsmentioning
confidence: 99%
“…Окисний стрес, що при цьому виникає, су-проводжується порушенням молекулярних механізмів регуляторних процесів у клітині й призводить до зміни експресії окремих генів [1,3].…”
Section: вступunclassified